Expression and localization of gastrin messenger RNA and peptide in spermatogenic cells. - Schalling, M (1990)
In previous studies we have shown that the gene encoding cholecystokinin (CCK) is expressed in spermatogenic cells of several mammalian species. In the present study we show that a gene homologous to the CCK-related hormone, gastrin, is expressed in the human testis. The mRNA hybridizing to a human gastrin cDNA probe in the human testis was of the same size (0.7 kb) as gastrin mRNA in the human antrum. By in situ hybridization the gastrinlike mRNA was localized to seminiferous tubules. Immunocytochemical staining of human testis revealed gastrinlike peptides in the seminiferous tubules primarily at a position corresponding to spermatids and spermatozoa. In ejaculated spermatozoa gastrinlike immunoreactivity was localized to the acrosome. Acrosomal localization could also be shown in spermatids with electron microscopy. Extracts of the human testis contained significant amounts of progastrin, but no bioactive amidated gastrins. In contrast, ejaculated sperm contained mature carboxyamidated gastrin 34 and gastrin 17. The concentration of gastrin in ejaculated human spermatozoa varied considerably between individuals. We suggest that amidated gastrin (in humans) and CCK (in other mammals) are released during the acrosome reaction and that they may be important for fertilization.